The Importance of Integrating Environmental Security to Human Security Based Policy in Managing Humanitarian Crisis: The Case of the Lake Chad Basin - Kusumawardani, Natasya (President University, 2017)
Humanitarian crisis is one of the critical problems in international relations which threaten the security. Humanitarian crisis could be caused by many factors, either originated by human activities or environmental degradations. It changed the idea that threat could only be state related, but it could also directly be impacting the people. This article argues that in order to manage this problem, there is the need to shift the perspective in seeing security from traditional (state-centric) to non-traditional (people-centred) to build effective policy. It also argues that environmental security is a part of human security, both have close linkage of action and reaction. The case in the Lake Chad Basin shows that there is a threat to human security from the environment, either it is coming from the water crisis in the lake and the impact of climate change.